LB-100, a novel Protein Phosphatase 2A (PP2A) inhibitor, sensitizes malignant meningioma cells to the therapeutic effects of radiation. (28th February 2018) - Ho, Winson S.; Sizdahkhani, Saman; Hao, Shuyu; Song, Hua; Seldomridge, Ashlee; Tandle, Anita; Maric, Dragan; Kramp, Tamalee; Lu, Rongze; Heiss, John D.; Camphausen, Kevin; Gilbert, Mark R.; et al.
Abstract: Atypical and anaplastic meningiomas (AAM) represent 20% of all meningiomas. They are associated with poor outcomes due to their tendency to recur. While surgery and radiation (RT) are first line therapy, no effective systemic medical treatment has been identified. Protein phosphatase 2A (PP2A) is a ubiquitously expressed serine/threonine phosphatase involved in cell cycle regulation and DNA repair. Here, we examined radiosensitizing effects of LB-100, a novel inhibitor of PP2A against AAM as a novel treatment strategy. Three human-derived immortalized meningioma cell lines, IOMM-LEE, GAR, and CH-157, were used to investigate the radio-sensitizing potential of LB-100 in AAM. Survival fraction by clonogenic assay, immunofluorescence, cell cycle analysis and protein expression were evaluated in vitro. The antitumor effects of combining LB-100 with RT were verified in vivo by using intracranial orthotopic xenograft mouse model. Pharmacologic PP2A inhibition with LB-100 prior to RT enhanced the radiosensitivity of meningioma cells and reduced survival fraction in clonogenic assays. LB-100 increased DNA double-strand breakage (measured by γ-H2AX), mitotic catastrophe cell death, and G2/M cell cycle arrest in irradiated meningioma cells. Also, LB-100 decreased activation of STAT3 and expression of its downstream proteins. In vivo, LB-100 and RT combined treatment prolonged the survival of mice with xenografts compared to RT alone. Taken together, these results provide convincing preclinical data to support the use of LB-100 as a radiosensitizing agent for treatment of malignant meningioma. Its potential for clinical application deserves further investigation. Highlights: Inhibition of Protein Phosphatase 2A Inhibitor (PP2A) enhances the cytotoxic effect of radiation in meningioma cells. PP2A inhibition increases radiation induced DNA double-strand breakage, mitotic catastrophe and G2/M cell cycle arrest. PP2A inhibition decreases activation of STAT3 and expression of its downstream proteins. Combining PP2A inhibition with radiation significant increased survival of mice with meningioma xenograft.